1988
DOI: 10.4315/0362-028x-51.8.648
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Aerobic Spore-Formers and Bacillus cereus in Meat Product Additives

Abstract: Microbial populations in 225 samples of meat product additives including spices, seasoning, proteins, starch, salt, sugar and colorants, were enumerated by means of aerobic plate counts (APC), aerobic spore counts (ASC), Bacillus cereus total counts (BcTC), and B. cereus spore counts (BcSC). Our data indicate that meat product additives with the exception of sugar and salt were contaminated mainly by aerobic spore-formers including B. cereus under spore-forming conditions. To improve the quality of meat produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The original basis for meat fermentation was preservation by the inhibition or restriction of microbial decomposition. Meat-product additives, which include spices, seasonings, proteins, starch and colorants, have also been shown to be contaminated with B. cereus (Shinagawa et al 1988). Herbs and spices widely used in foods harbor B. cereus (Garcia et al 2001;Freire and Offord 2002;Banarjee and Sarkar 2003).…”
Section: Presence and Identification Of Bacillus Cereus In Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…The original basis for meat fermentation was preservation by the inhibition or restriction of microbial decomposition. Meat-product additives, which include spices, seasonings, proteins, starch and colorants, have also been shown to be contaminated with B. cereus (Shinagawa et al 1988). Herbs and spices widely used in foods harbor B. cereus (Garcia et al 2001;Freire and Offord 2002;Banarjee and Sarkar 2003).…”
Section: Presence and Identification Of Bacillus Cereus In Meatmentioning
confidence: 99%
“…Bacillus cereus is a common contaminant of many foodstuffs, especially of cereals (Chung and Sun 1986;Higuti et al 1997), milk and milk products (Ahmed et al 1983;Wong et al 1988;Giffel et al 1995) and dried ingredients such as herbs and spices (Czech et al 2001;Garcia et al 2001). The occurrence of B. cereus as a meat contaminant was reported by many investigators not only in raw meat (Goepfert et al 1972;Johnson 1984;Nel et al 2004), but also in meat products (Sooltan et al 1987;Nortjé et al 1999) and meatproduct additives (Shinagawa et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…starch, and colorants are more likely to be exposed to B. cereus because these additives have also been shown to be contaminated with B. cereus (Shinagawa et al, 1988). In this study, we identified 2 main control points for preventing food poisoning by B. cereus contamination of RTE sandwiches and Kimbab.…”
Section: Discussionmentioning
confidence: 94%